Immunobiology of Steroid-Unresponsive Severe Asthma - Marshall, Courtney Lynn; Hasani, Kosovare; Mookherjee, Neeloffer (Frontiers in Allergy, 2021)
Asthma is a heterogeneous respiratory disease characterized by airflow obstruction, bronchial hyperresponsiveness and airway inflammation. Approximately 10% of asthma patients suffer from uncontrolled severe asthma (SA). A major difference between patients with SA from those with mild-to-moderate asthma is the resistance to common glucocorticoid treatments. Thus, steroid-unresponsive uncontrolled asthma is a hallmark of SA. An impediment in the development of new therapies for SA is a limited understanding of the range of immune responses and molecular networks that can contribute to the disease process. Typically SA is thought to be characterized by a Th2-low and Th17-high immunophenotype, accompanied by neutrophilic airway inflammation. However, Th2-mediated eosinophilic inflammation, as well as mixed Th1/Th17-mediated inflammation, is also described in SA. Thus, existing studies indicate that the immunophenotype of SA is diverse. This review attempts to summarize the interplay of different immune mediators and related mechanisms that are associated with airway inflammation and the immunobiology of SA.